First report of Candida auris in Guangdong, China: clinical and microbiological characteristics of 7 episodes of candidemia - Peng, Yaqin; Liu, Yue; Yu, Xuegao; Fang, Jingchun; Guo, Zhaowang; Liao, Kang; Chen, Peisong; Guo, Penghao (Emerging microbes & infections, 2024)
is an emerging multidrug-resistant fungal pathogen worldwide. To date, it has not been reported in Guangdong, China. For the first time, we reported 7 cases of candidemia from two hospitals in Guangdong. The clinical and microbiological characteristics of these cases were investigated carefully. Two geographic clades, i.e. III and I, were found popular in different hospitals by whole genome sequencing analyses. All isolates from bloodstream were resistant to fluconazole, 5 of which belonged to Clade III harbouring VF125AL mutation in the gene. The isolates with Clade I presented Y132F mutation in the gene as well as resistance to amphotericin B. All isolates exhibited strong biofilm-forming capacity and non-aggregative phenotype. The mean time from admission to onset of candidemia was 39.4 days (range: 12 - 80 days). Despite performing appropriate therapeutic regimen, 42.9% (3/7) of patients experienced occurrences of candidemia and colonization after the first positive bloodstream. colonization was still observed after the first candidemia for 81 days in some patient. Microbiologic eradication from bloodstream was achieved in 85.7% (6/7) of patients at discharge. In conclusion, this study offers a crucial insight into unravelling the multiple origins of in Guangdong, highlighting great challenges in clinical prevention and control.